STUDY ON MENTAL HEALTH PROBLEMS AND COUNTERMEASURES OF COLLEGE STUDENTS UNDER THE BACKGROUND OF EPIDEMIC PREVENTION AND CONTROL - Chao, Bohong; Fan, Jianwu (Psychiatria Danubina, 2021)
To explore the mental health problems and countermeasures of college students under the background of epidemic prevention and control. A total of 286 students in school were investigated with self-designed social demographic questionnaire, epidemic cognitive behavior, epidemic panic and anxiety questionnaire, depression symptom group scale, heart-filling scale and emotion regulation self-efficacy scale. College students have a certain understanding of COVID-19 transmission routes, preventive measures, etc., and can actively cooperate and understand the country's epidemic prevention measures. The average score of the College Student Anxiety Self-Rating Scale is (55.37±6.13) points. The total score of students' emotional regulation self-efficacy is 64.32±10.61, the total score of expressing positive emotions is 24.17±3.55, and the total score of managing negative emotions is 39.69±7.71. Under the epidemic situation, the degree of bad emotions such as panic, anxiety and depression is lower. The mental health status of college students is on the decline. According to the demographic characteristics and anxiety sources of different students, more social support and targeted and personalized intervention measures should be given to promote their positive mental state.